Awareness of University students' for disaster risk reduction according to Sendai International Framework (Journal of the College of Basic Education, 2022)
The aims of the research is knowing the reality of awareness according to Send Sendai framework for reduction disaster risk for students of Mosul University/ College of education for pure Sciences/ Department of Life Sciences/first stage. The researchers used the descriptive approach for its suitability with research. The research community consists of (264) students from the first stage of Life Sciences Department/ College of Education for pure Sciences, the sample of the research is(160) students The researchers also built a measure of awareness for reduction disaster risk which consist (68) paragraph as a tool for collecting data and the virtual validity was confirmed for scale and used a suitable statistical means and applying the scale on the core of the research sample, Then the researchers concluded that there is a depression in the awareness level of disaster risk reduction and this due to the lack of inclusion of Sendai framework in school curricula therefore the researchers recommend using all methods agreed internationally within Sendai framework .Also the researchers recommend that a similar studies should be undertaken to measure awareness of disaster risk reduction for students at all levels of education.